(untitled) (Solukhumbu Multiple Campus Research Journal, 2025)
This study examines head teachers’ experience regarding decisions at institutional level. Particularly, it aims to explore the decision-making processes of head teachers in Nepal’s community secondary schools, highlighting the lived experiences and ethical dilemmas that influence institutional decisions. We employed narrative inquiry to generate information from the participants. Altogether, four participants were selected from different parts of Nepal. Using a narrative inquiry approach, we talked directly to head teachers whose stories show that making decisions is much more than a technical or policy-driven act; it is a deeply human process shaped by personal values, the culture of the organization, and the weight of community expectations. Even though policy changes call for participatory governance, our research shows that decision making power is still often centralized and that stakeholder involvement is often limited or just for show. Head teachers had ongoing problems like political interference, lack of resources, and bureaucratic inertia, but they showed resilience and an unwavering commitment to the well-being of their students. Their stories show how policy ideals don’t always match up with real life. By focusing on decision-making that fits the local context and is guided by ethical and inclusive values, this study adds to our understanding of educational leadership in challenging settings. For the future, both research and policy should aim to close the gap between what is written in policies and what happens in practice. This can be achieved by encouraging teamwork, building leadership skills, and making everyone more accountable. These efforts will help Nepal’s schools move closer to offering fair, high-quality education for all students. Policymakers must make the rules clearer so that head teachers know what they can decide in the right way, Protect head teachers from unfair political interference. They should be given useful training for professional growth that will help conflict resolution, using the latest technology, and be capable of making the right decision to solve the problem. Head teachers must influence others by making the right decision. Finally, Parents, SMC members, students and the community will also provide support for the head teacher’s fair and transparent decisions.